Calcium Glycerolate Catalyst Derived from Eggshell Waste for Cyclopentadecanolide Synthesis - Cheng, Haijun; Wei, Jiangli; Liang, Min; Dai, Suyi; Liu, Xiongmin; Ma, Li; Wang, Hongyun; Lai, Fang (Frontiers in Chemistry, 2021)
The synthesis costs of macrolide musks are higher than those of other commercial musks. To make this process less expensive, eggshell waste was calcined at a low temperature to obtain a catalyst for the cyclopentadecanolide production via reactive distillation using a glycerol entrainer. X-ray diffraction, Fourier-transform infrared spectroscopy, scanning electron microscopy, transmission electron microscopy, and X-ray photoelectron spectroscopy analyses of the original and recovered catalysts revealed that the main catalytic ingredient was calcium glycerolate (CaG) and not calcium diglyceroxide (CaDG). The basic strengths of CaG and CaDG obtained by Hammett indicators were 7.2 < H_≤ 15.0 and 9.8 < H_≤15.0, while the corresponding base amounts were 1.9 and 7.3 mmol/g, respectively. Because CaG was soluble in glycerine, the catalyst was efficiently reused. The reaction product containing over 95.0 % cyclopentadecanolide with a yield of 49.8 % was obtained at a temperature of 190 °C and catalyst amount of 12 wt.% after 7 h of reaction. Thus, eggshell waste may be directly placed into the reaction mixture after calcination at 600 °C to synthesise a large amount of cyclopentadecanolide within a relatively short time. The results of this work indicate that eggshell waste can serve as a potential eco-friendly and affordable catalyst source for the production of macrolide musks.